(untitled) (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. Combined efforts of farmers, rice scientists, extension personnel and Government of Bangladesh have yielded clean rice growth rate of 0.34 million ton (MT) year-1 during 2009-10 to 2013-14 in the country. In 2014-15, the country acquired a rice surplus of about 2 MT. However, maintaining the current surplus of rice in the coming decades is a great challenge. Authentic estimation of future rice requirement and future resource availability would guide to way forward. This paper presents rice vision for Bangladesh leading to 2050 and beyond. In this study, secondary data from different government-owned statistics and research institutes were collected, analyzed and synthesized to develop models and/or model parameters to generate outputs such as future population, rice production and rice requirement. Population of Bangladesh will reach 215.4 million in 2050, when 44.6 MT of clean rice will be required. With the pace of rice-production-increase in the last five years, production can reach 47.2 MT, having a surplus of 2.6 MT in 2050. The study sets 2.6 MT as the target for clean rice surplus every year leading to 2050 and beyond. Several hurdles, such as increasing population, decreasing resources and increasing climate vulnerability, can hinder achieving the target. Three major interventions?accelerating genetic gain, minimizing yield gap and curtailing adoption lag?are proposed to break the barriers to achieve the target. Major challenges to implement the interventions include shrinking net cropped area, decreasing availability of irrigation water and increasing pressure on soil fertility. Smart technology such as, location specific variety, profitable cropping sequences, innovative cultural management, and mechanization coupled with smart dissemination using multiple means would ease production barriers. We recommend a number of measures, such as, guaranteeing a minimum cropped area, accelerating the rate of genetic gain in varietal development and intensifying collaboration among the stakeholders to reduce adoption lag of newly released promising rice varieties, to achieve the rice vision of Bangladesh leading to 2050 and beyond. Bangladesh Rice j. 2015, 19(2): 1-18